Faktor yang Mempengaruhi Ketepatan Anggaran Sektor Publik - Fajar Saputro; Bambang Setyobudi Irianto; Eliada Herwiyanti (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2016)
Budgets implementation of local goverment in Indonesia has always been a concern of stakeholders, the budget accuration phenomenon is one of them. Local budgets implementation in Indonesia always produce SILPA, namely the excess of budget with the realization, the facts indicate inaccuracies of local budget implementation. This research was conducted in order to empirically demonstrate the role of external pressures, environmental uncertainty, organizational commitment and budget quality of budget accuracy.The research method uses quantitative methods with explanatory approach, data collection conducted by using questionaire and distributed to echelon 4 officials who involved in planning, implementating, monitoring, controling and evaluating of budget in Cilacap local goverment, use purposive sampling methode to get research sample and using Warp PLS 0.4 as a test tool statistics. The results showed that external pressure and environmental uncertainty has a negative significant effect on budget accuracy and commitment of the organization and budget quality has a positive significant effect on budget accuracy.This study contributes to local governments to improve budget accuracy by optimizing the organizational commitment and budget quality, and also raise awareness in light of external and environmental uncertainty wisely. Another contribution is that this study provides academic benefits for the development of theory in public sector accounting.